2022
DOI: 10.3389/fpsyt.2022.939856
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy in the treatment of anorexia nervosa: Its effects depending on the type of physical exercise—A systematic review

Abstract: Background and purposeClinical research focusing on the effectiveness of exercise therapy (ET) in patients with anorexia nervosa (AN) shows increasing interest in the last decade. The aim of this systematic review was to provide an overview of quantitative studies that have examined the impact of ET in AN patients and to examine its specific effects on physical and mental health according to the type of physical exercise (PE) practiced.MethodsThe review was carried out based on the PRISMA 2020. Electronic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The current literature review supports previous positive findings from studies on effects from psychoeducation and supervised PAE during treatment of different EDs. However, because the existing studies on safety and effects from use of PAE in treatment of EDs is limited in number, the same articles are cited and evaluated in reviews published the past decade [ 32 34 , 43 ▪ , 44 , 46 , 47 ▪ , 48 ▪ ]. Hence, the more recent original studies [ 45 ▪▪ , 50 ▪▪ , 51 , 52 , 53 ▪▪ ] bring important nuances and findings to the field, and the feasibility and safety of education and practical experience from PAE during treatment that they demonstrate are underlined by the positive experiences from those with lived experiences [ 54 , 55 ▪▪ , 56 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current literature review supports previous positive findings from studies on effects from psychoeducation and supervised PAE during treatment of different EDs. However, because the existing studies on safety and effects from use of PAE in treatment of EDs is limited in number, the same articles are cited and evaluated in reviews published the past decade [ 32 34 , 43 ▪ , 44 , 46 , 47 ▪ , 48 ▪ ]. Hence, the more recent original studies [ 45 ▪▪ , 50 ▪▪ , 51 , 52 , 53 ▪▪ ] bring important nuances and findings to the field, and the feasibility and safety of education and practical experience from PAE during treatment that they demonstrate are underlined by the positive experiences from those with lived experiences [ 54 , 55 ▪▪ , 56 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…The three reviews (all of only anorexia nervosa) and one metanalysis (all EDs) that summarized findings on including supervised exercise to treatment, were similar in characterizing exercise programs as low-to-moderate in impact; that exercise gave no effect on body weight or –composition compared with a control condition; and, that exercise had either positive or neutral effects on psychopathology (Table 2) [46–49]. Importantly, no adverse outcomes were reported.…”
Section: What Are the Effects From Including Physical Activity Or Exe...mentioning
confidence: 92%
See 1 more Smart Citation
“…Anorexia nervosa (AN) refers to an eating disorder that leads to abnormal low body weight and anxiety related to gaining weight accompanied by distorted self-perception of one's own body. With regard to treatment, AN has been commonly targeted through psychotherapy, physical exercise, and pharmaceutical interventions as a joint intervention [37,38]. Interestingly, deep brain stimulation (DBS) of the subcallosal cingulate has been well tolerated and shown to be associated with improvements in mood and anxiety in patients with treatment-refractory AN [39].…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…However, due to the high incidence of dysfunctional exercise in patients with ED, some specialists prefer to limit physical activity during treatment [78]. Nevertheless, a growing number of studies have shown that incorporating physical activity into the routine care of these patients can improve ED symptomatology and can be an effective intervention for the management of these disorders [79][80][81][82][83][84]. Experienced clinicians have reaffirmed the need to incorporate physical activity into ED treatment protocols within a psychotherapeutic approach, not only for the physical and mental health benefits but also to help patients learn how to engage in exercise in an adaptive manner [85].…”
Section: Predictive Factors Of Therapeutic Successmentioning
confidence: 99%